The Importance of Increasing Knowledge About Worm Infection and Hemoglobin (Hb) Testing as An Efforts To Prevent Anemia in Students of Cikiwul 2 Elementary School, Bantar Gebang, Bekasi - Diah Lestari; Bagya Mujianto; Nova Hardianto; Dewi Inderiati; Citra Amaniah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Worm infection occurs when eggs or larvae enter the body, the worm parasites attach to the intestinal mucosa, suck blood chronically, resulting in significant blood loss. In addition, worms interfere with nutrient absorption (malabsorption), causing deficiencies in iron, folate, and protein, which are essential for hemoglobin formation, thus causing anemia. Infections often occur in elementary school students due to limited knowledge about worm invasion. Community service activities with the Community Partnership Program (CPP) Science and Technology Scheme, The Importance of Increasing Knowledge About Worm Infections and Hemoglobin (Hb) Examination as an Effort to Prevent Anemia in Students of SDN Cikiwul 2, Bantar Gebang, Bekasi. The target group is 102 students in grades 5 and 6.The method of increasing knowledge through pre-test and post-test using a questionnaire, and measuring Hemoglobin (Hb) levels using a Point of Care (POCT) tool. Determination of anemia categories based on cut-offs by WHO in the Guideline on Hemoglobin Cut-offs to Define Anaemia in Individuals and Populations.The results of the activity showed an increase in students' knowledge of worms, from 74.8 in the pre-test to 81.3 in the post-test. The proportion of students with a score of 70 or above also increased, from 68.6% in the pre-test to 82.4% in the post-test. The average HB level was 12.3 g/dL, with a minimum of 9.4 g/dL and a maximum of 16.3 g/dL. The overall prevalence of anemia remains relatively high (32.3%), with mild anemia predominating (18.6%). No students were found to have severe anemia. Male students tended to have anemia more often (40%), with 24.0% having mild anemia compared to female students. The age of students experiencing anemia ranged from the age group > 12 years at 48.3%, with 34.5% being in the mild anemia category. The proportion of 5th grade students with anemia was 36.3%, with 22.7% being in the mild anemia category. The results indicate the potential for continued accumulation of nutritional deficiencies.